Brain perfusion single photon emission computed tomography abnormality in MRI-negative stroke-like patients post COVID-19 vaccination. Issue 47 (25th November 2022) - Tepmongkol, Supatporn; Suwanwela, Nijasri C.; Hirankarn, Nattiya; Tangwongchai, Sookjaroen; Vorasayan, Pongpat; Sukprakun, Chanan; Siritaranon, Natakorn; Kijpaisalratana, Naruchorn; Akarathanawat, Wasan; Chutinet, Aurauma; Tantivatana, Jarturon
Abstract : Stroke-like symptoms after COVID-19 vaccination was thought to be functional if there was no anatomical image abnormality. We aimed to analyze brain perfusion changes in these patients. A case-control study of brain perfusion single photon emission computed tomography (SPECT) of 12 vaccinated patients with left-sided stroke-like symptoms were compared with 12 age- and gender-matched normal interictal brain SPECTs using voxel-based analysis. Significant hyperperfusion was seen on the right side in postcentral, inferior parietal, mid temporal, parahippocampal, and caudate regions, and on the left side in the thalamus, hippocampus, and mid temporal areas. In addition, there were hypoperfused bilateral superior frontal gyri and right mid/posterior cingulate cortex (Family-wise-error corrected p -values < .05). Both hypoperfusion and hyperperfusion in the brain are demonstrated. We hypothesize that these findings might be the result of the functional neurological disorder. However, based on other previous studies, circulating spike protein in the patients' plasma early after vaccination might also be the cause.